2018
DOI: 10.5455/aim.2018.26.240-244
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Proliferation of Cancer Cells from Breast Cancer Patients

Abstract: Introduction:The most cases of cancer death, which are in the first rank among cancers suffered by women is breast cancer. The breast cancer therapy for patients has been done, but still not optimal, so it is necessary to understand the mechanism of therapy in model cell of breast cancer.Aim:This study aim to develop an isolation technique of breast cancer cell from patients as a cancer cell model.Material and methods:Breast cancer cell isolation is performed by enzymatic methods using the collagen I and hyalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In the last years, several isolation protocols of breast (cancer) tissue cells have been developed and reported . These differ in complexity as well as repeatability.…”
Section: List Of Taqman® Assays (Primer‐probe Sets) Used In This Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, several isolation protocols of breast (cancer) tissue cells have been developed and reported . These differ in complexity as well as repeatability.…”
Section: List Of Taqman® Assays (Primer‐probe Sets) Used In This Workmentioning
confidence: 99%
“…In the last years, several isolation protocols of breast (cancer) tissue cells have been developed and reported. 1,2 These differ in complexity as well as repeatability. In this work, we describe a new simple, efficient, and reproducible protocol for isolation and culturing of breast cancer cells from triple-negative breast cancer (TNBC) tissue.…”
mentioning
confidence: 99%
“…+ has capability for unlimited self-renewal and has good ability to initiate and drive brain tumor in vivo [9] and CD133 positivity also has high correlation with survival and chemoresistance in gliomas [18]. However, one study also found that there are CD133-negative (CD133 − ) CSCs in gliomas that exhibit similar property as CD133 + CSCs [19].…”
Section: Discussionmentioning
confidence: 99%
“…For IDH-1, R132H mutant if stained was negative or < 10% categorized as negative and if > 10% as positive. PD-L1 IHC results were defined on the tumor proportion score as follows based on distributions as 0 (negative), 1 (<20%), 2 (20-50%), 3 (50-80%), 4 (>80%); score for intensity as 0 (negative), 1 (weak), 2 (moderate), and 3 (strong); results from distribution x intensity as histoscore low (0-4), moderate (4-6), and high (6)(7)(8)(9)(10)(11)(12).…”
Section: Immunohistochemical Staining For In Vitro Glial Fibrillary Amentioning
confidence: 99%
See 1 more Smart Citation